Too Scared to Go Sick: Precarious Academic Work and 'Presenteeism Culture' in the UK Higher Education Sector During the Covid-19 Pandemic. (June 2022) - Hadjisolomou, Anastasios; Mitsakis, Fotios; Gary, Steven
This article discusses the story of Steven, a precarious academic worker, and his decision to work from home while being infected with Covid-19; a phenomenon called virtual presenteeism. As argued, Steven's sickness presence is the outcome of the increasing precarity and job insecurity in the sector, as well as the outcome of a presenteeism culture in academia which is being facilitated by technology and the blended learning approach adopted during the pandemic. The article outlines precarious academic workers' fear to go off sick, illustrating how Steven negotiates the precarity of his contract via virtual presenteeism to portray over-commitment to the institution and avoid the risk of job loss. As concluded, while blended learning becomes the new educational norm in higher education, virtual presenteeism risks becoming the new attendance norm. This article calls for more research to examine how the blended teaching approach will further impact on academic work, post-pandemic.